Innovations in Engineering Education and the Role of Professors’ Mentality - V. Livshits (Образование и наука)
The paper presents the psychological cluster profile of the Higher School professorial staff – the leading modernization component of engineering education. The professorial corps’ attitude to innovation is considered regarding its divergent character. The detailed analysis of both the subjective and objective factors determining such position toward the innovation in engineering education has been done for the first time. The methodology of the research compiles the experience of several Higher Schools in different countries along with the conceptual suggestions. In the contemporary situation, the international and federal standards define the strategic guidelines for modernizing the engineering education aimed at developing the professional competences of the graduates. Therefore, the tactics of achieving such goals become a priority. However, in many cases, the good tactic plans do not work well because of the insufficient attention given to the professors’ mentality. The understanding of the underlying causes of the professorial staff resistance and opposition to the process can provide the top managers with the reliable instruments for control and elimination of such divergent trends in any module of engineering education.The research findings will facilitate the development of the engineering education system along with its modules towards the re-engineering – the new trend related to the innovative modernization of engineering education.